Multiplex gene expression profile in inflamed mucosa of patients with Crohn’s disease ileal localization: A pilot study - Giudici, Francesco (World J Clin Cases, 2019)
BACKGROUND: Crohn’s disease (CD) is a complex disorder resulting from the interaction of genetic, environmental, and microbial factors. The pathogenic process may potentially affect any segment of the gastrointestinal tract, but a selective location in the terminal ileum was reported in 50% of patients. AIM: To characterize clinical sub-phenotypes (colonic and/or ileal) within the same disease, in order to identify new therapeutic targets. METHODS: 14 consecutive patients undergoing surgery for ileal CD were recruited for this study. Peripheral blood samples from each patient were collected and the main polymorphisms of the gene Card15/Nod2 (R702W, G908R, and 1007fs) were analyzed in each sample. In addition, tissue samples were taken from both the tract affected by CD and from the apparently healthy and disease-free margins (internal controls). We used a multiplex gene assay in specimens obtained from patients with ileal localization of CD to evaluate the simultaneous expression of 24 genes involved in the pathogenesis of the disease. We also processed surgery gut samples with routine light microscopy (LM) and transmission electron microscopy (TEM) techniques to evaluate their structural and ultrastructural features. RESULTS: We found a significant increase of Th17 (IL17A and IL17F, IL 23R and CCR6) and Th1 (IFN-γ) gene expression in inflamed mucosa compared to non-inflamed sites of 14 CD patients. DEFB4 and HAMP, two genes coding for antimicrobial peptides, were also strongly activated in inflamed ileal mucosa, suggesting the overwhelming stimulation of epithelial cells by commensal microbiota. IFN-γ and CCR6 were more expressed in inflamed mucosa of CD patients with ileal localization compared with patients with colonic localization suggesting a more aggressive inflammation process in this site. Morphological analysis of the epithelial lining of Lieberkün crypts disclosed enhanced release activity from goblet mucocytes, whereas the lamina propria contained numerous cells pertaining to various lines. CONCLUSION: We observed that the expression of ileal genes related to Th1 and Th17 activity is strongly activated as well as the expression of genes involved in microbiota regulation.